Prevalence and Factors Associated with Depression among High School Students in Ho Chi Minh City, Vietnam - Cao, Lieu Xuan; Le, Cong Minh; Tran, Diu Thi Thu; Nguyen, Vu Hoang Anh; Tran-Chi, Vinh-Long (National Journal of Community Medicine, 2024)
Background: Depression in high school students is a common mental health problem and requires evaluation for early intervention. The study was carried out to determine the prevalence of depression symptoms and associated characteristics among high school students in Ho Chi Minh City, Vietnam. Methods: This cross-sectional study enrolled participants between February 2022 and June 2022. The instrument utilized was a questionnaire of socioeconomic-demographic variables, educational characteristics, and the self-reported depression scale obtained from the Centre for Epidemiological Studies-Depression (CES-D). Results: 384 high school students (165 males and 219 females) were questioned. The CES-D had a mean score of 17.3, with 57.6% of participants reporting depressed symptoms. The frequency was 63.3% among male students (OR = 1.84, 95% CI = 1.19-2.83, p = .005). Multiple logistic regression revealed that adolescents with poor health, weak friendships, limited participation in school activities, family problems, financial worries, and negative educational environments were significantly more likely to experience depressive symptoms (odds ratios ranging from 1.60 to 9.97, confidence intervals spanning 1.03 to 78.05, and p-values from <.001 to .044). Conclusion: The study emphasized the necessity of health promotion programs that target mental health awareness, improve social support networks, and introduce stress reduction techniques in schools to reduce the prevalence of depression among teenagers in Ho Chi Minh City, Vietnam.